The economics of gender and mental illness - Marcotte, David E. (Research in human capital and development ;, 2004)
While gender has so often been found to be an important determinant of prevalence and outcomes of mental illness, economists have rarely focused on gender differences as a central element of their analyses. In this volume, we direct the focus of research in the economics of mental health squarely on the topic of gender. Each paper in this volume provides insight into the ways in which women and men are afflicted and affected by mental illness in the labor market. This volume will provide the reader with a richer understanding of prevalence of mental disorders, the educational, employment and earnings impacts of psychiatric disease, and prospects for treating and providing access to health care for the mentally ill.